Examining Voter Turnout: A Look at Participatory Budgeting and Political Participation in Romania - Alexandru Andrei Ivan; Sorana Alexandra Constantinescu; Gabriel Bădescu (Transylvanian Review of Administrative Sciences, 2025)
The gap between elected authorities and citizens is widening in many democracies due to declining political engagement. This article examines whether participatory budgeting (PB) is linked to voter turnout in Romania. As a widely used deliberative mechanism in public administration, PB’s potential impact on voter behavior remains debated. This study contributes empirical evidence from Romania, addressing a gap in the international literature where previous findings on PB’s effect on voter turnout are mixed. Focusing on the 2024 local elections, the analysis employs regression techniques to assess the relationship between PB presence and voter turnout, with previous election turnout and population changes as control variables. The results show a positive but statistically insignificant relationship between PB and turnout, which may be attributed to the limited impact of PB projects in Romania, marked by low local authority involvement, weak public engagement, and minimal project outcomes.